Antisperm antibodies: invaluable tools towards the identification of sperm proteins involved in fertilization - Vazquez, Monica Hebe (2014)
The identification of sperm proteins involved in fertilization has been the subject of numerous investigations. Much interest has been dedicated to naturally occurring antisperm antibodies (ASA) and their impact in fertility. Their presence in men and women has been associated with 2-50% of infertility cases. ASA may impair pre- and post-fertilization steps. Experimental models have been developed using sperm proteins as immunogens to evaluate their involvement in sperm function. Our team has pursued investigations to assess ASA presence in biological fluids from patients consulting for infertility and their effect on fertilization. We found ASA in follicular fluids with ability of inducing the acrosome reaction and blocking sperm-zona pellucida interaction and used them to identify sperm entities involved in these events. We generated and utilized antibodies against proacrosin/acrosin to characterize the sperm protease system. We implemented an ELISA to detect proacrosin/acrosin antibodies in human sera and evaluated their impact upon fertility by developing in vitro assays and a gene immunization model. This review presents a summary of ASA history, etiology, current approaches for detection and effects upon fertility. ASA (naturally occurring, generated by animal immunization and/or of commercial origin) are invaluable tools to understand the molecular basis of fertilization, better diagnose/treat immunoinfertility and develop immunocontraceptive methods.